Relations Between Dual Filial Piety and Life Satisfaction: The Mediating Roles of Individuating Autonomy and Relating Autonomy - Sun, Peizhen; Fan, Xiaoyue; Sun, Yudi; Jiang, Hongyan; Wang, Lu (Frontiers in Psychology, 2019)
Filial piety (FP) is a culture-specific Confucian concept that specifies how children should treat their elders. It is one of the virtues to be held above all else in eastern cultures, which plays an irreplaceable role in shaping intergenerational relationships and affecting individual’s psychological development. This study aimed to examine simultaneously the effects of reciprocal FP and authoritarian FP on life satisfaction, and the mediating roles of individuating autonomy and relating autonomy therein. To do this, 360 high school students in China were surveyed. Subsequently, a mediation model based on the Dual Filial Piety Model and previous studies was tested. Results demonstrated that reciprocal FP predicted life satisfaction positively, and both individuating autonomy and relating autonomy played significant mediating roles in the relationship between reciprocal FP and life satisfaction. Moreover, authoritarian FP had a negative indirect effect on satisfaction through the mediating role of individuating autonomy, while authoritarian FP exerted a positive indirect effect on satisfaction through the mediating role of relating autonomy. Theoretical and practical implications of these findings are discussed.